Sistem Informasi Penjualan Pempek Palembang Berbasis Website dengan Model Rapid Application Development - Jodi Hariyan; Said Imam Puro; Kevin Apriana; Eva Zuraidah (TIN: Terapan Informatika Nusantara, 2023)
The development approach used in this project is the RAD method, which involves structured stages starting from planning, analysis, design, implementation, testing, to delivery. which focuses on Pempek products to promote their products efficiently, providing easy ordering services for users who want to buy Pempek products. This application allows sellers to market their products easily through clear product images, descriptions, and prices, users can quickly find the Pempek products they are looking for and place orders easily, with this application, it is hoped that Pempek sales shops can develop and gain exposure larger ones, while users can easily use the PHP programming language and use MySQL, Pempek Palembang Online, the distribution of its products which still uses a conventional system found several problems that often occur, one of which is still manual, therefore with the application it is hoped that it can make it easier for customers to buy the products they need, and of course make it easier for companies to transact with their customers. Quickly and Efficiently, without having to come directly to the seller's location.